2007
DOI: 10.1063/1.2729563
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of friction under forging conditions by means of the ring-on-disc test

Abstract: In order to understand the tribological processes and interactions in the tool-workpieceinterface systematically, basic experiments that allow an independent variation of influencing parameters are necessary. The ring-on-disc test is a popular model experiment that is often used in tribological analyses at low normal contact pressures.The scope of the paper is an analysis of the applicability of the ring-on-disc test for high normal pressures as used in forging processes, using aluminium AA6082 as workpiece ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Previous investigators working with DLC have reported wear performance of the DLC coatings using pin-on-disc, ballcratering, reciprocating ball-on-plate and ring-on-disc apparatus (7)(8)(9)(10). Results have shown large variations in the wear properties owing to different deposition techniques, coating thickness above adhesion layer, type of metal substrate and experimental conditions (8,11). Buchner et al (11) also reported that the material and chemical properties of DLC coatings can be tailored by controlling the composition and deposition techniques utilised.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators working with DLC have reported wear performance of the DLC coatings using pin-on-disc, ballcratering, reciprocating ball-on-plate and ring-on-disc apparatus (7)(8)(9)(10). Results have shown large variations in the wear properties owing to different deposition techniques, coating thickness above adhesion layer, type of metal substrate and experimental conditions (8,11). Buchner et al (11) also reported that the material and chemical properties of DLC coatings can be tailored by controlling the composition and deposition techniques utilised.…”
Section: Introductionmentioning
confidence: 99%